The Capacity Assessment of Lower-Class Municipalities in Agriculture Services Towards Full Devolution - Laurio, Nenette M.; Malto, Erwin H. (Future Science / FSH-PH Publications, 2023)
In response to Mandanas Ruling, President Duterte signed Executive Order 138 which mandates the local government unit to formulate their Devolution Transition Plans (DTP) from FY2022 to FY2024. The DTP charted the capacity development agenda of every Local Government Unit and National Government Agency to prepare for full devolution in FY2024. This study covers 11 municipalities in the province of Masbate that belonged to the 4th and 5th classes in terms of income. It aims to identify the capacity development agenda to create a baseline for the capacity development program of the lower-classes municipalities towards full devolution. Specifically, this study highlighted the current state of capacity, the desired state, the alignment of these capacity development agenda to DILG, and, finally, the priority capacity interventions in response to the full devolution of the Agriculture sector. This study used qualitative and descriptive research approaches. An extensive document scrutinising of the Devolution Transition Plans was structured in each municipality. The study concede that lower-class municipalities have a low capacity to assume devolved services mandated in Section 17 of RA 7160 and other devolution laws in the sector of Agriculture and Extension Services. There are capacity gaps with the proposed specific capacity development agenda. The capacity development agenda were categorized into six (6) capacity pillars. These are the useful baseline in crafting the National Agencies’ Capacity Development Program.